Phylogeny and recombination of new world begomoviruses - Pereira, Hermano Monteiro de Barros (2017)
The genus Begomovirus (family Geminiviridae) includes viruses with mono- and bipartite genomes of circular, single-stranded DNA (ssDNA), which infect dicot plants and are transmitted by the whitefly Bemisia tabaci. Begomoviruses constitute an important group of plant pathogens responsible for severe losses in several crops of economic importance, mainly in tropical and subtropical regions. Based on phylogenetic relationships and genomic organization, begomoviruses can be divided into New World (NW) and Old World (OW) groups. NW begomoviruses have mostly bipartite genomes, with the two components named DNA-A and DNA-B. Recently, the association of a small number of NW begomoviruses with alphasatellites was demonstrated. Begomoviruses evolve at high rates, compared to viruses with RNA genomes. Although it is well established that mutation and recombination are the main sources of genetic variability for these viruses, a better understanding of the evolutionary forces that act upon begomovirus populations is still lacking. The objectives of this study were: (i) to obtain more detailed information on the evolutionary mechanisms that influence the genetic variability of NW begomoviruses; (ii) to assess, phylogenetically, the effect of recombination on the evolution of NW begomoviruses; (iii) to measure, by phylogeographic analysis, the effect of migration on the diversification of NW begomoviruses. Datasets including all DNA-A and DNA-B reference sequences of NW begomoviruses were obtained from GenBank. Recombination analysis revealed a relationship between NW begomoviruses and alphasatellites, suggesting that recombination is an important evolutionary mechanism affecting DNA-A evolution, particularly of the Rep gene ( present in both agents). Removal of recombinant blocks from the datasets was shown to be unnecessary, as it did not affect the phylogenetic signal when reconstructing phylogenies. Clusters among species were observed based on their locals of origin, suggesting that the introduction/migration of genomes from different areas greatly contributes to recombination and reassortment, which would increase the probability of the emergence of new variants better adapted than their parental viruses. Phylogeography results suggest that the DNA-A and DNA-B have distinct evolutionary histories, since they have ixdifferent common ancestors. Together, the results indicate an important role of recombination in the diversification of NW begomoviruses.